The Dynamics of Saturn's Main Aurorae. Issue 17 (10th September 2019) - Bader, A.; Badman, S. V.; Cowley, S. W. H.; Yao, Z. H.; Ray, L. C.; Kinrade, J.; Bunce, E. J.; Provan, G.; Bradley, T. J.; Tao, C.; Hunt, G. J.; Pryor, W. R.
Abstract: Saturn's main aurorae are thought to be generated by plasma flow shears associated with a gradient in angular plasma velocity in the outer magnetosphere. Dungey cycle convection across the polar cap, in combination with rotational flow, may maximize (minimize) this flow shear at dawn (dusk) under strong solar wind driving. Using imagery from Cassini's Ultraviolet Imaging Spectrograph, we surprisingly find no related asymmetry in auroral power but demonstrate that the previously observed "dawn arc" is a signature of quasiperiodic auroral plasma injections commencing near dawn, which seem to be transient signatures of magnetotail reconnection and not part of the static main aurorae. We conclude that direct Dungey cycle driving in Saturn's magnetosphere is small compared to internal driving under usual conditions. Saturn's large‐scale auroral dynamics hence seem predominantly controlled by internal plasma loading, with plasma release in the magnetotail being triggered both internally through planetary period oscillation effects and externally through solar wind compressions. Plain Language Summary: Saturn's main aurorae are thought to be generated as a result of sheared plasma flows near the boundary between the rapidly rotating magnetosphere of Saturn and interplanetary space. It is often assumed that the steady flow of the solar wind away from the Sun has an impact on this flow shear; due to the direction of Saturn's rotation the aurorae would then have to be brighter at the planet's dawnside than on its duskside, which was observed in previous studies. Here we analyze a large set of auroral images taken by Cassini's ultraviolet camera, but we cannot find any sign of such an asymmetry. This indicates that the impact of the solar wind on Saturn's aurorae must be smaller than previously thought and that they must instead mainly be controlled from within the system. This assumption is supported by our observations of bright auroral patches at dawn, which are likely a signature of plasma being released from Saturn's magnetosphere and appear at quite regular periods corresponding to Saturn's rotation period. Key Points: A dawn‐dusk asymmetry in Saturn's auroral emissions due to Dungey cycle activity is not observed under typical solar wind driving The previously observed statistical intensity maximum near dawn is the result of large‐scale auroral plasma injections from Saturn's nightside The phasing of these auroral injections indicates that magnetotail reconnection seems to partly be governed by planetary period oscillations